Amyloid β and Amyloid Precursor Protein Synergistically Suppress Large-Conductance Calcium-Activated Potassium Channel in Cortical Neurons - Yamamoto, Kenji; Yamamoto, Ryo; Kato, Nobuo (Frontiers in Aging Neuroscience, 2021)
Intracellular amyloid β (Aβ) injection suppresses the large-conductance calcium-dependent potassium (BK) channel in cortical pyramidal cells from wild-type (WT) mice. In 3xTg Alzheimer’s disease (AD) model mice, intraneuronal Aβ is genetically programmed to accumulate, which suppresses BK channel. However, the mode of BK channel suppression remained unclarified. The present report revealed that only one (11A1) of the three anti-Aβ-oligomer antibodies that we examined, but not anti-monomer-Aβ-antibodies, was effective in recovering BK channel activity in 3xTg neurons. Antibodies against amyloid precursor protein (APP) were also found effective, suggesting that APP plays an essential part in this Aβ-oligomer-induced BK channel suppression in 3xTg neurons. In WT neurons, by contrast, APP suppressed BK channels by itself, which suggests that either APP or Aβ is sufficient to block BK channels, thus pointing to a different cooperativity of Aβ and APP in WT and 3xTg neurons. To clarify this difference, we relied on our previous finding that the scaffold protein Homer1a reverses the BK channel blockade in both WT and 3xTg neurons. In cortical neurons from 3xTg mice that bear Homer1a knockout (4xTg mice), neither anti-APP antibodies nor 11A1, but only the 6E10 antibody that binds both APP and Aβ, rescued the BK channel suppression. Given that Homer1a expression is activity dependent and 3xTg neurons are hyperexcitable, Homer1a is likely to be expressed sufficiently in 3xTg neurons, thereby alleviating the suppressive influence of APP and Aβ on BK channel. A unique way that APP modifies Aβ toxicity is thus proposed.